The Catalytic Role of Transformational Principal Leader-ship in Enhancing Islamic Religious Education Teacher Performance via Professional Competence: A Dual-Site Case Study in West Java - Yati Rumiati R; Ahmad Sukandar (Journal of Science and Education (JSE), 2026)
In the landscape of modern education, the performance of Islamic Religious Education (PAI) teachers is pivotal not only for academic transmission but for the moral fortification of students against the volatility of globalization. This study investigates the strategic influence of school principal leadership on PAI teacher performance, mediated by the enhancement of professional competence. Employing a qualitative case study design at SMPN 1 Pacet and SMPN 2 Cipanas, West Java, data were harvested through semi-structured interviews, participant observations, and extensive documentation analysis. The findings reveal a tripartite mechanism: (1) The Principal as a Transformational Architect, where leadership transcends administrative management to foster an intellectual and spiritual work climate; (2) The Trajectory of Competence Development, where principals actively facilitate continuous professional development (CPD) through supervision and digital integration; and (3) The Synergistic Manifestation of Performance, where enhanced competence translates into innovative, student-centered pedagogy. The study concludes that the principal's role is not merely supervisory but catalytic; effective leadership acts as the scaffold that converts potential teacher competence into kinetic educational performance. These findings advocate for a paradigm shift in principalship training towards instructional and transformational leadership models to sustain the quality of religious education.